Betting against the New: Early short selling post-IPO - Lee, Dongyoup; Wang, Shu Feng (Pacific Basin Finance Journal, 2025)
Short sellers consistently seek opportunities to profit by betting against overvalued stocks, and newly issued firms often exhibit overreaction due to IPO underpricing. This article investigates the initial short selling activities for IPO stocks in the Korean stock market, differentiated by investor types at the account level, and examines the profitability of these transactions. Contrary to common perceptions, short selling activities are not constrained immediately following an IPO, with the majority undertaken for speculative purposes. We find a positive relationship between the time to the first short sale and the first-day return, with regression analyses indicating that higher initial returns associated with IPO underpricing may prompt earlier participation by short sellers. While foreign investors remain the primary participants in short selling new firms, individual investors tend to profit from a select number of IPO stocks for which they possess relevant information. Our findings suggest that imposing a short selling ban, such as the one enacted during the COVID-19 pandemic, may inadvertently exacerbate stock market overreactions, potentially resulting in overvaluation by restricting the market's ability to correct inflated prices through short selling mechanisms.
Keywords: Initial public offering; Investor type; Korean stock market; Short selling